Endoscopic mucosal phenotypes and endoscopic Sydney system gastritis assessment in relation to Helicobacter pylori infection and upper digestive clinical signs: A 2‐year study among patients with gastroduodenal disorders in Cameroon - Lionel Danny Tali Nguefak; Ghislaine Florice Faujo Nintewoue; Ngimgoh Ngemeshe Stanley; Paul Talla; Ghislaine Ngatcha; Sartre Michele Tagni; Nzoume Nsope Mengang Jude‐Marcel; Dzoyem Jean Paul; Laure Brigitte Kouitcheu Mabeku (JGH Open)
Abstract Background and Aim Helicobacter pylori represents the major pathogen in the pathophysiology of diverse gastrointestinal conditions. This study sought to determine the endoscopic aspect of the gastric mucosa in relation to H. pylori infection in Cameroon. Methods This study was conducted in three reference health facilities in Cameroon from October 2020 to October 2022. The study enrolled 494 consecutive volunteer dyspeptic patients attending to the gastroenterology department of the selected health facilities. A description of the aspect of gastric mucosa of all participants was performed during endoscopy examination, and biopsies were collected for H. pylori detection using rapid urease tests. Results Gastritis, ulcerated lesions, duodenitis, esophagitis, normal mucosa aspect, bulbitis, and gastric neoplastic lesions were found in 40.1, 22.3, 10.9, 10.3, 9.7, 6.3, and 0.40% of biopsy samples, respectively. Erythematous/exudative (45.9%) and enterogastric reflux (12.2%) were the main gastritis types recorded. H. pylori was present in 58.1, 46.3, 87.1, 66.7, and 61.8% in gastritis, duodenitis, bulbitis, esophagitis, and ulcerated lesions, respectively. A positive relationship was noticed between the presence of H. pylori and gastritis (1.037 [0.720–1.493]; P = 0.845), bulbitis (4.237 [1.602–11.235]; P = 0.004), esophagitis (1.515 [0.822–2.793]; P = 0.183), ulcerated lesions (1.233 [0.798–1.904]; P = 0.345), erythematous/exudative gastritis (1.354 [0.768–2.389]; P = 0.295), and enterogastric reflux gastritis (1.159 [0.492–2.733]; P = 0.736). Conclusion Gastritis and erythematous/exudative gastritis are the most frequent gastrointestinal pathophysiology conditions in dyspeptic patient in our milieu. H. pylori infection is responsible for 94.8% of the gastrointestinal pathophysiology conditions with bulbitis as the condition is significantly associated with this bacterium infection.